Kajian Konsentrasi Iaa dan Bap pada Multiplikasi Pisang Raja Bulu In Vitro dan Aklimatisasinya - Eddy Tri Haryanto; Retno Bandriyati Arniputri; Endang Setia Muliawati; Ellyvia Trisnawati (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2018)
Banana is a tropical fruit plant that popular in people. The availability of Raja Bulu banana seedling insufficient to cover the needs. Problems in commercial banana cultivation is the least availability of clonal superior seeds. Multiplication in tissue culture technique can potentially overcome all limitations of Raja Bulu conventional seedling. So that, the objective of this research was to multiplicate an amount of Raja Bulu banana shoot using plant growth regulator in MS medium to initially produce shoot organs. The multiplication was done by Completely Randomized Design with 2 factor of IAA (0; 0,5; 1 ppm) and BAP (0, 2, 4 ppm). The data were analyzed by ANOVA and the mean compared using Duncan’s pairwise comparisons at p = 0,05. The acclimatization was design by Completely Randomized Block Design with 3 different media of palm fiber, bagasse, and banana pseudo stem then analyzed by ANCOV. The results showed there was interaction of IAA and BAP on variables at the appearance of shoots and the leaf appearance in multiplication. The medium without IAA and contained BAP 2 ppm showed the highest mean number of shoot but it was not cost effective with other treatment in this multiplication. Giving IAA 0,5 ppm with BAP 4 ppm accelerated when the shoots appear and when the leaves appear on multiplication Raja Bulu banana. There was no significant interaction or influence of IAA and BAP on plant height, leaf number, and pseudo stem diameter as acclimatization variable with 3 medium used. The percentage of acclimatization success is 76,5%.